A practicum report on the activities done at the fishermen's training center. - Lasa, Virgilio I. (Miagao, Iloilo College of Fisheries, University of the Philippines, 1981)
Fisheries is an applied science, therefore, it is imperative for a fisheries student to undergo a period of apprenticeship or practicum, to expose him to proper training in his own field. My practicum at the fishermen's training center in Sangley Point, Cavite City gave me substantial experience, insights, and an overall view that marine fisheries is a very qualitative field of science. It basically deals with marine biology, oceanography, marine science and ecology, navigation, fisheries statistics and the basic technical subjects in marine freshwater. Furthermore, the training was widely disseminated to imbue fisheries consciousness to the trainees. It also gave a clearer picture of the significance and role of the fishing industry in this growing economy. This practicum report gives an insight of the various activities I undertook during the six months period of my training which included bother the theoretical and practical aspects of Marine Fisheries like our sea-training.
Keywords: Fish-culture.